Quadriceps short-term resistance exercise in subjects with resistant hypertension - Arthur de Sá Ferreira; Juliana Flávia de Oliveira; Ivan Cordovil; José Barbosa Filho
INTRODUCTION: Resistant arterial hypertension may lead to muscle disuse and reduced functional capacity due to arterial and target-organs lesions. The main objective of this work is to evaluate the quadriceps strength and fatigue tolerance after a program of resistance exercise in subjects with resistant primary hypertension. METHODS: Six patients under pharmacological treatment were submitted to a four-week resistance exercise training program for the quadriceps (8-14 repetitions, 3 sets, 3 days per week). Strength was evaluated by isometric dynamometry, as the percentage change in maximum voluntary contraction over the four week program. Fatigue was analyzed by surface electromyography, as the change in both root mean square value and intercept of median frequency slope of vastus medialis and vastus lateralis. RESULTS: Significant increase in the maximum voluntary contraction was observed (p = 0.04). Fatigue tolerance was not improved as seen by root mean square as well as in the intercept of median frequency (p > 0.05). Additionally, no significant changes were observed in resting arterial blood pressure and heart rate throughout the training period. CONCLUSION: The prescribed protocol seemed to successfully increase localized muscle strength without negatively affecting the monitored cardiovascular variables in patients with resistant hypertension under pharmacological treatment.